SQL in a Nutshell, 4th Edition - Kline, Kevin, 1966-; Obe, Regina O.; Hsu, Leo S. (O'Reilly Media, Inc., 2022)
For programmers, analysts, and database administrators, this Nutshell guide is the essential reference for the SQL language used in today's most popular database products. This new fourth edition clearly documents SQL commands according to the latest ANSI/ISO standard and details how those commands are implemented in Microsoft SQL Server 2019 and Oracle 19c, as well as in the MySQL 8, MariaDB 10.5, and PostgreSQL 13 open source database products. You'll also get a concise overview of the relational database management system (RDBMS) model and a clear-cut explanation of foundational RDBMS concepts--all packed into a succinct, comprehensive, and easy-to-use format. Sections include: Background on the relational database model, including current and previous SQL standards Fundamental concepts necessary for understanding relational databases and SQL commands An alphabetical command reference to SQL statements, according to the SQL:2016 ANSI standard The implementation of each command by MySQL, Oracle, PostgreSQL, and SQL Server An alphabetical reference of the ANSI SQL:2016 functions and constructs as well as the vendor implementations Platform-specific functions unique to each implementation.